Fiksasi Bambu Gombong dan Tali Fixation of Gombong and Tali Bamboos - Wahyu Dwianto; Toshiro Morooka; Misato Norimoto (Masyarakat Peneliti Kayu Indonesia, 2004)
This research describes stress relaxation measurement to understand the fixation mechanism of compressive deformation of water saturated Gombong bamboo (Gigantochloa pseduarundinaceae) and Tali bamboo (Gigantochloa apus). Stress relaxations are measured by compressing the specimens in radial direction to 0.2 strains between 110ºC and 190ºC for various periods of time in electro oil hydraulic testing system equipped with an autoclave, which was heated by high temperatures saturated steam. The stress approximately disappears in 60min at 170ºC, in 30min at 180ºC, and in 20 min at 190ºC for Gombong bamboo. On the other hand, the fastest release of stress is found for Tali bamboo. The plots of relationship between residual stress and strain recovery of Gombong and Tali bamboos lay on a single curve, respectively. The relationship is similar to that of Sugi wood by heating. However, the weight loss of the two bamboos is extremely higher than that of wood. The fixation is achieved at a weight loss of 20% for Gombong and Tali bamboos. From these results, the fixation mechanism is considerably dominated by the decomposition of hemicelluloses and lignin.